2022
DOI: 10.1016/j.wombi.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the COVID-19 pandemic on birth satisfaction in a prospective cohort of 2,341 U.S. women

Abstract: Problem Birth satisfaction is an important health outcome that is related to postpartum mood, infant caretaking, and future pregnancy intention. Background The COVID-19 pandemic profoundly affected antenatal care and intrapartum practices that may reduce birth satisfaction. Aim To investigate the extent to which pandemic-related factors predicted lower birth satisfaction. Methods 2,341 women who were recruited pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 57 publications
1
23
0
2
Order By: Relevance
“…Additionally, mothers (14.5% to 97%) were made to wear masks or even PPE during labour, birth, breastfeeding and throughout their hospital stay regardless of their COVID-19 status [35] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , 13% of mothers were annoyed by having to wear PPE during labour [35] , [48] . Another mother shared how the mask-wearing impaired mother-child bonding, as her newborn was unable to see her face [50] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, mothers (14.5% to 97%) were made to wear masks or even PPE during labour, birth, breastfeeding and throughout their hospital stay regardless of their COVID-19 status [35] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , 13% of mothers were annoyed by having to wear PPE during labour [35] , [48] . Another mother shared how the mask-wearing impaired mother-child bonding, as her newborn was unable to see her face [50] .…”
Section: Resultsmentioning
confidence: 99%
“…Restricted access to maternity healthcare services was associated with a higher risk of psychological distress and mental health impairment [62] . In-person appointments were often suspended, rescheduled, or converted to virtual or telemedicine [31] , [37] , [49] . The suspension of in-person pregnancy-related services led to some mothers giving up on pregnancy care [31] , [37] , and caused others to feel anxious, neglected, sad, frustrated [37] , lonely [30] , and fearful of not receiving desired treatment [63] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This meant maintaining and reinforcing restrictions within the hospital, not only for COVID-19-infected women, but preventively for all others, since vaccination had not yet been started in pregnant women [ 26 ]. These restrictions and changes in care are associated with low satisfaction with care received [ 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot affirm the cause of this result, although it could be because the actual companion was not who was chosen prior to childbirth; we found somewhat lower satisfaction scores among women whose companion was not who they had initially chosen. A prospective longitudinal study carried out at the beginning of the pandemic found that restrictions on companions negatively affected satisfaction, along with other factors, such as the stress perceived by the woman or the use of a mask [ 27 ]. No other factors related to satisfaction were found in this study; however, other previous studies found that a lower level of education is associated with greater satisfaction [ 14 ], that the type of childbirth influences satisfaction [ 30 , 32 ] and that spontaneous onset of labor is associated with higher satisfaction [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%